The plasma morphology of an asymmetric electrode ablative pulsed plasma thruster. (26th February 2019) - Zhang, Zhe; Ling, William Yeong Liang; Ren, Junxue; Tang, Haibin; Cao, Jinbin; Lin, Xin; York, Thomas M
Abstract: The ablative pulsed plasma thruster (APPT) is a typical form of electric propulsion that is highly suitable for micro-satellites. However, its low performance has been a main drawback. Recently, an asymmetric segmented anode schematic was shown to enhance the performance of APPTs. The improved thrust performance obtained with the use of a segmented anode can potentially enable promising applications in future space tasks. To further understand the physical processes behind a segmented anode APPT, experiments using an ultra-high-speed camera, narrow bandpass filters, and a magnetic probe were conducted with both normal parallel-plate electrodes and a segmented anode on an experimental APPT. Successive images of light emission from C +, neutral C2, and broadband emission reveal the evolution of the plasma morphology on an APPT with a segmented anode. The magnetic field strength profiles show that the inter-electrode plasma propagation velocity of a segmented anode APPT is approximately 19 km s −1, which is slightly lower than that of a normal APPT at 23 km s −1 . However, the similar order of magnitude suggests a similar downstream acceleration mechanism between the two. The arc morphology observed in the high-speed images shows that the segmented anode APPT with asymmetric electrodes has a restricted arc attachment point, possibly resulting in stronger arc current density at the anode corner. This should result in higher ionization and ablation when compared with a normal anode APPT. Based on the results here, we hypothesize that the segmented anode APPT may be able to better utilize the restrike energy in the propellant ionization process. This fundamentally changes the physical process behind APPT operation, meaning that the improvements should also be applicable to other APPT designs. It can also be adopted as an additional step in the overall optimization of an APPT design.